2021
DOI: 10.1109/access.2021.3133279
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Voltage Subharmonics on Line Start Permanent Magnet Synchronous Motor

Abstract: This project is financially supported under the framework of a program of the Ministry of Science and Higher Education (Poland) as "Regional Excellence Initiative" in the years 2019-2022, project number 006/RID/2018/19, amount of funding 11 870 000 PLN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
(83 reference statements)
0
18
1
1
Order By: Relevance
“…Table 1 lists the nameplate parameters of the LSPMSM, and Figure 1 shows a photograph with the mounted accelerometer. Because of some modifications, the results of vibration measurements presented in this study cannot be directly compared with previous research [36,37]. mum shock level peak of 5100 g, and weight of 14.5 g).…”
Section: Measurement Setupmentioning
confidence: 91%
See 4 more Smart Citations
“…Table 1 lists the nameplate parameters of the LSPMSM, and Figure 1 shows a photograph with the mounted accelerometer. Because of some modifications, the results of vibration measurements presented in this study cannot be directly compared with previous research [36,37]. mum shock level peak of 5100 g, and weight of 14.5 g).…”
Section: Measurement Setupmentioning
confidence: 91%
“…In addition, previous research [5,[35][36][37][38] indicated high transverse vibration of the rotating machinery for no-load, while in other load conditions, the observed vibration was generally moderate. At the same time, at least temporarily, many motors carry a load much less than rated [42,43], but this is not typical.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations